Utilizing Lean Management Techniques to Improve Head CT Scan Turnaround Time of Ischemic Stroke Patients in the Emergency Department of Dr. Mohammad Hoesin Hospital, Palembang - Marisdina, S; Junadi, P (KnE Life Sciences, 2018)
Stroke is the most common neurological problem encountered in an emergency department. The management of acute stroke in an emergency department in South Sumatra has not been the most important standard of examination in the diagnosis of stroke, especially ischemic stroke. Thrombolytic therapy was performed on patients within 3 hours after onset. The process of CT Scan of head at the arrival department of Emergency Department Mohammad Hoesin Hospital Palembang takes 4 hours from arrival to examination[1], while according to the guideline, it should take no more than 25 minutes [2]. The application of lean method is expected to improve the service quality for ischemic stroke patients in emergency departments. This study used an operational study method with lean management approach in accordance with the head CT scan evaluation of ischemic stroke patients in emergency departments. The evaluation started from the triage until the head CT scan examination. This study was conducted at the Mohammad Hoesin Hospital Palembang emergency department from November until December 2016. Primary data were collected from direct observation as well as interviews with informants, while secondary data were obtained with document search, patient service flow charts and other related data in emergency departments. Current value stream map showed that the CT scan turnaround time was 175.41 minutes, in 87.8% were waste activities (non-value-added), 6.9% were value-added activities and 5.26% were NVA but necessary. After utilizing lean management techniques, simulated value stream map showed significant decrease in lead time to 30.09 minutes, followed by increased in value-added activities and percentage of non-value-added activities. The results of this study are in accordance with what was disclosed by McManus [3] and Eitel [4] that the lean principle on increasing the percentage of value-added activities and reducing waste, thus providing considerable success in improving the quality of emergency room services. Lean management technique successfully improves the head CT scan turnaround time of ischemic stroke patients in the emergency department. Keywords: lean management, value streaming map, value-added, non-value-added